Hyperuricaemia, gout and related adverse events associated with antihypertensive drugs: A real-world analysis using the FDA adverse event reporting system - Xue-Feng Jiao; Xue-Feng Jiao; Xue-Feng Jiao; Xue-Feng Jiao; Kunpeng Song; Xueyan Jiao; Hailong Li; Hailong Li; Hailong Li; Hailong Li; Linan Zeng; Linan Zeng; et al. (Frontiers Media S.A., 2023)
Background: The role of antihypertensive drugs in inducing hyperuricaemia and gout has been a long-term concern in clinical practice. However, clinical studies regarding this issue are limited in number and have yielded inconsistent results. We comprehensively evaluated the association between various antihypertensive drugs and the occurrences of hyperuricaemia, gout and related adverse events (AEs) using the FDA Adverse Event Reporting System (FAERS), aiming to guide the selection of antihypertensive drugs with a goal of minimizing the risk of hyperuricaemia, gout and related AEs.Methods: We used OpenVigil 2.1 to query the FAERS database. Hyperuricaemia, gout and related AEs were defined by 5 Preferred Terms: hyperuricaemia, gout, gouty arthritis, gouty tophus and urate nephropathy. Disproportionality analysis was performed, and a positive signal indicated an association between AEs and antihypertensive drugs.Results: The numbers of antihypertensive drugs with positive signals for hyperuricaemia, gout, gouty arthritis, gouty tophus and urate nephropathy were 46, 66, 27, 8 and 6, respectively. These drugs included diuretics, antihypertensive drugs with central action, α blockers, β blockers, α and β blockers, calcium channel blockers, angiotensin converting enzyme inhibitors, angiotensin II receptor blockers, renin inhibitors, vasodilators, and compound preparations. Furthermore, 42 antihypertensive drugs had positive signal for more than one AEs.Conclusion: Our study suggests that some potassium-sparing diuretics, calcium channel blockers and losartan may be associated with increased risk of hyperuricaemia, gout or related AEs, which is inconsistent with most previous studies. Moreover, Our study also suggests that some antihypertensive drugs with central action, α and β blockers, renin inhibitors and vasodilators may be associated with increased risk of hyperuricaemia, gout or related AEs, which has not been reported in previous studies. These findings complement real-world evidence on the potential risks of hyperuricaemia, gout and related AEs associated with antihypertensive drugs.